Enhancing interprofessional student practice through a case-based model. Issue 4 (July 2013) - Cahill, Mairead; O'Donnell, Marie; Warren, Alison; Taylor, Ann; Gowan, Olive
Abstract : Healthcare workers are increasingly being called upon to work collaboratively in practice to improve patient care and it seems imperative that interprofessional working should be mirrored in student education, especially during placements. This short report describes a qualitative evaluation of a client-centered, case-based model of interprofessional education (IPE) which aimed to improve interprofessional communication and team working skills for the students and therapists involved in practice placements. The IPE project implemented the meet, assess, goal set, plan, implement, evaluate (MAGPIE) framework for interprofessional case-based teaching (Queensland-Health (2008)) alongside the International Classification of Function, Disability and Health (ICF) (WHO, 2001). Three separate focus groups explored the experiences of the students, therapists and placement facilitators from the disciplines of occupational therapy, physiotherapy and speech and language therapy. Three themes emerged: IPE as a motivating experience, IPE enhancing the depth of learning and clarity of expectations. This report concluded that IPE in the clinical setting, using the client-centered MAGPIE model, provided a strong foundation for enhanced learning in practice education contexts.